Temperature-dependent physiological and biochemical responses of the marine medaka Oryzias melastigma with consideration of both low and high thermal extremes. (December 2015) - Li, Adela J.; Leung, Priscilla T.Y.; Bao, Vivien W.W.; Lui, Gilbert C.S.; Leung, Kenneth M.Y.
Abstract: This study aimed to investigate temperature effect on physiological and biochemical responses of the marine medaka Oryzias melastigma larvae. The fish were subjected to a stepwise temperature change at a rate of 1 °C/h increasing or decreasing from 25 °C (the control) to six target temperatures (12, 13, 15, 20, 28 and 32 °C) respectively, followed by a 7-day thermal acclimation at each target temperature. The fish were fed ad libitum during the experiment. The results showed that cumulative mortalities were significantly increased at low temperatures (12 and 13 °C) and at the highest temperature (32 °C). For the survivors, their growth profile closely followed the left-skewed 'thermal performance curve'. Routine oxygen consumption rates of fish larvae were significantly elevated at 32 °C but suppressed at 13 and 15 °C (due to a high mortality, larvae from 12 °C were not examined). Levels of heat shock proteins and activities of malate dehydrogenase and lactate dehydrogenase were also measured in fish larvae exposed at 15, 25 and 32 °C. The activities of both enzymes were significantly increased at both 15 and 32 °C, where the fish larvae probably suffered from thermal discomfort and increased anaerobic components so as to compensate the mismatch of energy demand and supply at these thermal extremes. Coincidently, heat shock proteins were also up-regulated at both 15 and 32 °C, enabling cellular protection. Moreover, the critical thermal maxima and minima of fish larvae increased significantly with increasing acclimation temperature, implying that the fish could develop some degrees of thermal tolerance through temperature acclimation. Highlights: Growth of marine medaka larvae followed a left-skewed thermal performance curve. Oxygen consumption rate of the fish larvae increased with increasing temperatures. The fish larvae increased anaerobic components at the cold and warm extremes. Heat shock proteins (hsp70, hsp90) were up-regulated at the two thermal extremes. Thermal acclimation could enlarge thermal tolerance of the fish larvae.